Metal Complexes of 4-and 5-methoxy-2-Benzothiazolamine - Tewari, S.P.; Tripathi, P.; Santra, P.K. (Asian Journal of Chemistry, 2010)
Complexes of zinc(II), cadmium(II) and mercury(II) with 4-methoxy-2-benzothiazolamine (4-MeBT) and 5-methoxy-2-benzothiazolamine (5-MeBT), ML2X2 (M═Zn and X═Cl, Br, I; M═Cd and X═Cl, I L-4-MeBT or 5-MeBT), MLX2 (M═Cd and X═Br; M═Hg and X═Cl, Br, I, L═4-MeBT or 5-MeBT) have been synthesized and characterised on the basis of physico-chemical data. The electrical conductivity values in DMF and acetone reveal their non-electrolytic nature in solution and the spectral evidence indicates that the ligands are coordinated to the metal atoms through the amino nitrogen.